205k views
0 votes
F(x) = 2x^2-7x-7
g(x) = x+1

Find f(g(x))

2 Answers

2 votes

Answer:


2x^(2) -3x-12

Explanation:

To solve composite functions, figure out which function is on the "inside" and the outside":

f(x) is the inside and g(x) is the outside

Now plug the value of g(x) into the x values of f(x):


2(x+1)^(2)-7(x+1)-7

Then distribute following the steps of PEMDAS:


2(x^(2)+2x+1)-7x-7-7


2x^(2) + 4x + 2 - 7x -14

Then combine like terms:


2x^(2) -3x-12

User Pak Uula
by
4.7k points
4 votes

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️


f(x) = 2 {x}^(2) - 7x - 7


g(x) = x + 1

_________________________________


f(g(x)) = 2 ({x + 1})^(2) - 7(x + 1) - 7 \\


f(g(x)) = 2( {x}^(2) + 2x + 1) - 7x - 7 - 7 \\


f(g(x)) = 2 {x}^(2) + 4x + 2 - 7x - 7 - 7 \\

Collect like terms


f(g(x)) = 2 {x}^(2) + (4 - 7)x - 14 + 2 \\


f(g(x)) = 2 {x}^(2) - 3x - 12

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️

User Pcent
by
4.8k points